YAP pokreće razvoj kardiovaskularnih bolesti kod pacijenata sa reumatoidnim artritisom: Correlation between YAP and RA-CVD - Che, Guozhu; Liu, Ying; Zhang, Na; Zhao, Jing (Journal of Medical Biochemistry, 2023)
Background: To assess the influence of serum level of YAP on laboratory examination findings, imaging findings and disease activity of rheumatoid arthritis patients combined cardiovascular disease (RA-CVD).  Methods: RA-CVD patients (n=60), RA-nCVD patients (n=60) and healthy subjects (n=60) were recruited. Serum levels of YAP in them were detected by qRT-PCR. Their baseline characteristics were analyzed and compared. Disease activity, CVD risk factors and imaging findings in RA-CVD and RA-nCVD patients were evaluated and compared. In addition, potential influences of YAP on disease activity, CVD risk factors and imaging findings in RA-CVD patients were assessed. Results: RA-CVD patients had higher levels of ERS, anti-CCP, RF, HDL-C, CRP, FRS, BNP, LA, LVs, LVd and cIMT, and lower level of EF in comparison to RA-nCVD patients. Serum level of YAP was higher in RA-CVD patients than that of RA-nCVD patients and healthy subjects. YAP level was positively correlated to DAS28, TG, CRP, PLT, FRS, BNP and cIMT in RA-CVD patients. Conclusion: Serum level of YAP increases in RA-CVD patients. YAP is a potential factor driving the development of CVD in RA patients through regulating inflammatory response, lipid metabolism, glycometabolism and thrombosis.